Literary Text as an Illustrative Source of Meaning of Paradigms of «Success» in Pedagogy: E. Vodolazkin’s Novel «Brisbane» - Kalynych, Kateryna (Pedagogical Discourse, 2021)
Success is an important factor in the increase of teacher competence, its implementation as a person, as the professional approach to teaching provides not only the appropriate level of knowledge, but also affects the formation of individual qualities of students. Therefore, the image created by the teacher plays a fundamental role in teaching students, thus, this article shows the implementation of the paradigm of "success" through the prism of pedagogical image. Russian scientist and writer of Ukrainian origin Yevgeny Vodolazkin (1964), based on his own experience of studying in Soviet schools and universities, in the novel "Brisbane" emphasizes the most important qualities that a successful teacher must have. The factors create the image of a teacher who (does not) lead to educational success (a teacher-despot LesiaKirillovna, a teacher-romantic Vira Mykhailivna, favorite teacher of solfeggio Claudia Vasylivna, a teacher and a close friend Olena Markivna, inconspicuous Pavlo Sergeev ,a moralist-director of the school, a gossip teacher of social sciences, psychologically stable Katya, nonconformist Ivan Sergienko, experienced professor Besedin , a relative of Lisa). Instead, the peculiarity of the observance of ethical relations in the scientific community among fellow philologists can be traced through the character of Associate Professor Chukin. Through the prism of the image of the protagonist of the work - Glib Yanovsky -, the way of the formation of his pedagogical skill and professional perfection is considered. In particular, the significant influence of the experience of relationships with teachers on the teaching practice of the protagonist has been established. The difference between university and school teaching has a particular importance. It is proved that political ideology (in particular, of the Soviet Union) directly influences teaching practice. Based on opinion polls and the novel «Brisbane», it is highlighted the most necessary professional, individual features and appearance of the teacher to implement successful interaction with students and the paradigm of «success» in a professional manner, emphasizing the importance of pedagogical qualities needed by modern teachers .